Clustering of irrigated coffee access with best attributes to beverage - Celestino, Sonia Maria Costa; Malaquias, Juaci Vitória; Xavier, Manaira Ferreira Franco (Coffee Science - ISSN 1984-3909, 2015)
Embrapa Cerrados has an Active Germoplasm Bank of Coffea arabica L. compound of 900 access cultivated with the Controlled Water Stress technology with central pivot, 30 of theses accesses are productive. The aim of this work was to grouping these productive coffee access and to identify group (s) of access with the best attributes to beverage, besides to determine the relative contribution of the physical-chemical and chemical properties for the genetic divergence related to the beverage quality. The cherry coffee fruits of 30 cultivars were pre-processing by natural way. Part of coffee grains of 30 cultivars were submeted to light roasting and another part remains raw material. The Singh’s method was used to check how much the characteristics pH, total titratable acidity, soluble solids, protein and e polyphenols contribute for the genetic divergence observed among the 30 coffee access avaliable. The Cluster analysis promoted the organization of homogeneous coffee cultivars in four groups (Clusters). The homogeneity was based in the variation of values of the chemical and physicalchemical properties before and after the roasting, which compose the body and the sweetness of beverage (soluble solids), the acidity (total titratable acidity and pH), the flavor (polyphenols) and the aroma (protein), lowest soluble solids reduction, the greatest acidity increase, the lowest polyphenols increase and the greatest protein reduction desirable to the choice of quality coffees. The variable polyphenols had the highest contribution for the genetic divergence with 28,84%; pH, protein, soluble solids and acidity presented highlighted contributions of 19,23%, 19,11%, 17,79% and 15,03%, respectively. The group 4 constituted by access Icatu 2944, MG0188, MG1177 and Topázio was the most promising with respect to quality of beverage. These access were characterized by the greatest total titratable acidity increase and the highest protein reductions after roasting. This group also showed values of soluble solids reduction and polyphenols increasing more satisfactory to consumption than the others groups.